Cationic polyacrylamide alleviated the inhibitory impact of ZnO nanoparticles on anaerobic digestion of waste activated sludge through reducing reactive oxygen species induced. (15th October 2021) - Zhang, Baowei; Tang, Xiang; Fan, Changzheng; Hao, Wanle; Zhao, Yilin; Zeng, Yanjing
Highlights: Adding cationic polyacrylamide could weaken ZnO NPs toxicity on anaerobic digestion. Adding cationic polyacrylamide promoted solubilization and acidification process. The addition of cPAM recovered the performance of anaerobic digestion system. The presence of cPAM increased the abundances of dominant acidogens and methanogens. The mechanism relies on reactive oxygen species decreased. Abstract: The enrichment of zinc oxide nanoparticles (ZnO NPs) in waste activated sludge (WAS) has raised concerns about their potential impact on anaerobic digestion of WAS. To date, there is no information regarding how to attenuate the negative effects of ZnO NPs on WAS anaerobic digestion. In this study, it was found that the appropriate amount of cationic polyacrylamide (cPAM) could mitigate the toxicity of ZnO NPs. During short-term exposure, the supplement of 4.0 mg cPAM/g TSS significantly restored biochemical methane potential from 28.6% inhibition to 9.3% inhibition compared with the control digester ( P  < 0.01). The spiked cPAM promoted the solubilization and acidification stages by weakening the contact between ZnO NPs and anaerobes in anaerobic digestion process, thus providing abundant substance for sequent bio-utilization. In the long-term semi-continues operated reactor, the continuous replacement of cPAM (at 4.0 mg/g TSS) significantly strengthened the recovery of VS destruction rate (20.3% to 26.4%, P  < 0.01) and the daily yield of methane (93.5 mL/d to 124.2 mL/d, P  < 0.01). Consistent with the restored performance, the application of cPAM increased the total microbial communities and the relative abundances of dominant acidogens and methanogens. Further explorations showed decreased toxicity of ZnO NPs primarily attributed to the decline of reactive oxygen species (ROS) induced by ZnO NPs. Graphical abstract: Image, graphical abstract